2021
DOI: 10.1158/0008-5472.can-20-3543
|View full text |Cite
|
Sign up to set email alerts
|

ENO1 Promotes Lung Cancer Metastasis via HGFR and WNT Signaling–Driven Epithelial-to-Mesenchymal Transition

Abstract: ENO1 (α-enolase) expression is significantly correlated with reduced survival and poor prognosis in many cancer types, including lung cancer. However, the function of ENO1 in carcinogenesis remains elusive. In this study, we found that high expression of ENO1 is present in metastatic lung cancer cell lines and malignant tumors and is associated with poor overall survival of patients with lung cancer. Knockdown of ENO1 decreased cancer cell proliferation and invasiveness, whereas overexpression of ENO1 enhanced… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
60
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(63 citation statements)
references
References 51 publications
2
60
0
1
Order By: Relevance
“… 20 , 21 In lung cancer, for instance, ENO1 knockdown inhibited cancer cell proliferation and invasiveness, while ENO1 overexpression facilitated these processes. 22 Besides its function in glycolysis, ENO1 is also expressed as a cell surface plasminogen receptor and facilitates cancer cell adhesion and metastasis. 23 , 24 Interestingly, a previous work found that ENO1 expression was elevated in OSCC and increased cell proliferation, with circ-angiomotin like 1 acting as the upstream mediator.…”
Section: Introductionmentioning
confidence: 99%
“… 20 , 21 In lung cancer, for instance, ENO1 knockdown inhibited cancer cell proliferation and invasiveness, while ENO1 overexpression facilitated these processes. 22 Besides its function in glycolysis, ENO1 is also expressed as a cell surface plasminogen receptor and facilitates cancer cell adhesion and metastasis. 23 , 24 Interestingly, a previous work found that ENO1 expression was elevated in OSCC and increased cell proliferation, with circ-angiomotin like 1 acting as the upstream mediator.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies, including ours, reported that overexpression of glucose transporter 3 (GLUT3) promoted the EMT and invasiveness of glioma, colon, and breast cancer cells [37][38][39]. Additionally, ENO1 and LDHA were reported to promote the EMT and stemness in lung and breast cancer cells [40,41], suggesting that upregulation of glycolytic genes by YBX1 plays a crucial role in promoting tumor aggressiveness. In addition, YBX1 transcriptionally regulates a subset of mRNAs involved in the EMT, and YBX1 directly activates cap-independent translation of Snail [27].…”
Section: Discussionmentioning
confidence: 64%
“…One of two proteins, α-enolase, found on the surface of cells, was is involved in several key biological processes of cancer, including proliferation, migration and invasion [ 36 , 37 ]. According to previous reports, α-enolase was overexpressed in multiple tumors, including lung cancer [ 38 ], hepatocellular carcinoma [ 39 ], pancreatic cancer [ 40 ], and gastric cancer patients [ 41 ], and was proposed as a biomarker for early detection or prognosis [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…A recent study demonstrated that α-enolase and Annexin A1 autoantibodies could enhance diagnostic performance in lung cancers by combining CEA and CA125 [ 29 ]. Another study suggested that α-enolase could accelerate metastasis of lung cancer cell through HGFR and WNT signaling pathway, and presented a new antibody targeting α-enolase in lung cancer [ 37 ]. In multiple myeloma, α-enolase expression negatively correlated with overall survival, and targeting α-enolase could enhance immunity and improve outcome [ 46 ].…”
Section: Discussionmentioning
confidence: 99%